SBML Level 3: an extensible format for the exchange and reuse of biological models. Issue 8 (26th August 2020) - Keating, Sarah M; Waltemath, Dagmar; König, Matthias; Zhang, Fengkai; Dräger, Andreas; Chaouiya, Claudine; Bergmann, Frank T; Finney, Andrew; Gillespie, Colin S; Helikar, Tomáš; Hoops, Stefan; Malik‐Sheriff, Rahuman S; et al.
Abstract: Systems biology has experienced dramatic growth in the number, size, and complexity of computational models. To reproduce simulation results and reuse models, researchers must exchange unambiguous model descriptions. We review the latest edition of the Systems Biology Markup Language (SBML), a format designed for this purpose. A community of modelers and software authors developed SBML Level 3 over the past decade. Its modular form consists of a core suited to representing reaction‐based models and packages that extend the core with features suited to other model types including constraint‐based models, reaction‐diffusion models, logical network models, and rule‐based models. The format leverages two decades of SBML and a rich software ecosystem that transformed how systems biologists build and interact with models. More recently, the rise of multiscale models of whole cells and organs, and new data sources such as single‐cell measurements and live imaging, has precipitated new ways of integrating data with models. We provide our perspectives on the challenges presented by these developments and how SBML Level 3 provides the foundation needed to support this evolution. Abstract : Over the past two decades, scientists from different fields have been developing SBML, a standard format for encoding computational models in biology and medicine. This article summarizes recent progress and gives perspectives on emerging challenges.